Water intercalation strategy to fabricate low-potential and dense grapheme film anode for high energy density K-ion batteries. (20th January 2022) - Xu, Yali; Wu, Yuxuan; Tang, Qunli; Zhang, Xiangdan; Tang, Zhongfeng; Hu, Aiping; Fan, Zefu; Wang, Zhenling; Chen, Xiaohua
Abstract: Carbon materials have appealing potential as anode for Potassium ion batteries (KIBs), but achieving low-potential plateau curve and high energy density for anode materials is a primary challenge. Herein, a 3D holey reduced graphene oxide/ carbon nanotubes (L-HRGO/CNT) film was constructed via chemical etching and low- temperature drying method. The micro/mesoporous in graphene oxide (GO) sheets are created by chemical etching, which shorts ion transfer distance, and thus increases the K + intercalation/deintercalation rate. During low-temperature drying process, the water molecules inside the GO interlayer serve as self-sacrificial spacers for extending the stacked structure and maintaining integrity, increasing capacity contributed from K + intercalation for a low discharge voltage. And the CNTs introduced into the film via vacuum co-filtration can enhance the conductivity and mechanical strength of the film. The optimized L-HRGO/CNT film delivered a high K + storage capacity of 307.0 mA h g −1, high-rate capability, and the capacity retention reaches 72.6% at 200 mA g −1 for 200 cycles. When assembled with the KVPO4 F cathode, the reversible capacity remains 93.8 mAh g −1 after 100 cycles, and 473.0 Wh kg −1 (776.9 Wh L −1 ) of the energy density is achieved.